The significance of focally enhanced gastritis in haematopoietic stem cell transplant recipients. Issue 4 (21st June 2021) - Johncilla, Melanie; Elsoukkary, Sarah; Jessurun, Jose
Abstract : Aims: The histological diagnosis of acute gastric graft‐versus‐host‐disease (aGVHD) in patients with a history of haematopoietic stem cell transplant (HSCT) is based on the presence of epithelial cell apoptosis and karyorrhectic debris. There is, however, limited information on the histological findings in patients who develop symptoms several months after transplant. Focally enhanced gastritis (FEG), defined by the presence of focal periglandular lymphohistiocytic inflammation with neutrophilic or lymphocytic intra‐epithelial infiltration of gastric glands, has been described in patients with inflammatory bowel disease and in HSCT patients. The pattern closely resembles the focal periductal inflammation and lymphocytic exocytosis seen in chronic GVHD of the salivary gland. We sought to evaluate the significance of FEG in HSCT patients. Methods and results: Gastric biopsies from 151 HSCT patients who underwent endoscopies for GVHD‐like symptoms were identified. Time from transplant to biopsy, presence of extra‐gastric GVHD, medications and outcome were noted. Thirty‐five biopsies showed FEG and 21 showed aGVHD; the remainder were either normal or showed non‐specific changes. Twenty‐one (60%) FEG patients had concurrent histologically proven extra‐gastric GVHD. The time to biopsy in FEG patients was significantly longer than in aGVHD patients (162 versus 57 days, P  < 0.01). Prior or subsequent gastric biopsies of 14 patients in the FEG cohort were also evaluated and, of these, six showed aGVHD while one showed persistent FEG. Conclusions: These findings suggest that FEG probably represents a form of late‐occurring GVHD. This histological pattern should not be overlooked when identified in gastric biopsies from HSCT patients. Abstract :